Oxidative Dehydrogenation of Methane When Using TiO2- or WO3-Doped Sm2O3 in the Presence of Active Oxygen Excited with UV-LED - Shigeru Sugiyama (Catalysts, 2020)
There are active oxygen species that contribute to oxidative coupling or the partial oxidation during the oxidative dehydrogenation of methane when using solid oxide catalysts, and those species have not been definitively identified. In the present study, we clarify which of the active oxygen species affect the oxidative dehydrogenation of methane by employing photo-catalysts such as TiO2 or WO3, which generate active oxygen from UV-LED irradiation conditions under an oxygen flow. These photo-catalysts were studied in combination with Sm2O3, which is a methane oxidation coupling catalyst. For this purpose, we constructed a reaction system that could directly irradiate UV-LED to a solid catalyst via a normal fixed-bed continuous-flow reactor operated at atmospheric pressure. Binary catalysts prepared from TiO2 or WO3 were either supported on or kneaded with Sm2O3 in the present study. UV-LED irradiation clearly improved the partial oxidation from methane to CO and/or slightly improved the oxidative coupling route from methane to ethylene when binary catalysts consisting of Sm2O3 and TiO2 are used, while negligible UV-LED effects were detected when using Sm2O3 and WO3. These results indicate that with UV-LED irradiation the active oxygen of O2- from TiO2 certainly contributes to the activation of methane during the oxidative dehydrogenation of methane when using Sm2O3, while the active oxygen of H2O2 from WO3 under the same conditions afforded only negligible effects on the activation of methane.